Advances in hemiplegia rehabilitation: modern therapeutic interventions to enhance activities of daily living - Xiong, Jing; Wang, Jin-Tian; Lin, Shu; Xie, Bao-Yuan (Frontiers in Neurology, 2025)
Hemiplegia severely impairs patients’ abilities to perform activities of daily living (ADL), thus affecting their overall quality of life and independence. Often caused by stroke or other forms of brain injury, hemiparesis causes long-term impairment of upper and lower limb function, hindering the patient’s ability to manage self-care. With advances in modern rehabilitation medicine, emerging therapeutic interventions such as electrophysiological feedback, virtual reality, and robot-assisted therapy are increasingly being applied to the rehabilitation of hemiplegic patients. These interventions, combined with precise technical support through individualized training, have been shown to be effective in improving upper and lower limb function as well as enhancing ADL abilities of hemiplegic patients. This paper reviews recent advances in modern hemiplegic rehabilitation therapeutic interventions, assesses their impact on improving ADL performance, and examines their effectiveness in improving functional outcomes and quality of life for patients. These findings suggest that modern rehabilitation approaches have significant clinical potential to provide more personalized and effective treatment strategies for people with hemiplegia.